2014
DOI: 10.1016/j.jtcvs.2013.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Defining the best practice patterns for the neonatal systemic-to-pulmonary artery shunt procedure

Abstract: A substantial variation was found between hospitals in the rate of shunt-related complications. Centers with best outcomes implement aspirin earlier in their postoperative shunt thrombosis prophylaxis regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…32 A national database study examining best practices associated with systemic-to-pulmonary artery shunts found no difference in the use of postoperative heparin between centers with low or high incidences of shunt failure. 33 These studies did not consider differences in postoperative hematocrit. Large-scale, thoughtful investigations are clearly needed to determine the best perioperative management.…”
Section: Discussionmentioning
confidence: 99%
“…32 A national database study examining best practices associated with systemic-to-pulmonary artery shunts found no difference in the use of postoperative heparin between centers with low or high incidences of shunt failure. 33 These studies did not consider differences in postoperative hematocrit. Large-scale, thoughtful investigations are clearly needed to determine the best perioperative management.…”
Section: Discussionmentioning
confidence: 99%
“…Patient populations receiving SP shunts have changed considerably over the past 70 years, 7,8 but the rate of in-hospital mortality has changed little, from 8.1% in the earliest reports 9 to 4% to 10% in the higher-risk contemporary populations. 8,10,11 Major morbidity also remains common with SP shunts, with reintervention required in 7.3% of recipients and 3% to 6% requiring ECMO support.…”
Section: Discussionmentioning
confidence: 99%
“…Patient populations receiving SP shunts have changed considerably over the past 70 years, 7,8 but the rate of in-hospital mortality has changed little, from 8.1% in the earliest reports 9 to 4% to 10% in the higher-risk contemporary populations. 8,10,11 Major morbidity also remains common with SP shunts, with reintervention required in 7.3% of recipients and 3% to 6% requiring ECMO support. 11,12 We have analyzed a consecutive series of 169 infants and neonates requiring mechanical circulatory support in the form of veno-arterial ECMO, to ascertain the impact on outcomes of the presence of an SP shunt during ECMO support.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, those with single-ventricle physiology who require placement of a systemic-to-pulmonary artery shunt (e.g., modified Blalock-Taussig or central shunts) are at greatest risk, especially in the early post-operative period 3 , 4 , 5 . Consequently, this scenario has resulted in suboptimal post-operative outcomes as exemplified in a retrospective review of 2,058 neonates who underwent palliation with a systemic-to-pulmonary artery shunt at multiple centers; discharge mortality and complication rates were around an aggregate of 6.7% and 12.3%, respectively (6) . Early institution of aspirin, an irreversible inhibitor of platelet cyclooxygenase, is believed to be beneficial in reducing the risk of shunt occlusion and death 7 , 8 , but controversy remains regarding its overall effectiveness.…”
mentioning
confidence: 99%